Perception of Patients with Hypertension, Diabetes, or both Regarding Nursing Education upon Hospital Discharge (Boletín Semillero de Investigación en Familia, 2026)
Introduction: Inadequate discharge education among older adults contributes to preventable complications, unplanned returns to care, and diminished quality of life. Targeted health education is essential to support self-management after hospitalization. Objective: To describe patients’ perceptions of the education provided by nursing staff at discharge among individuals with hypertension, diabetes mellitus, or both. Materials and methods: We conducted a cross-sectional study using convenience sampling of 60 hospitalized patients with hypertension, diabetes mellitus, or both. Perceptions of discharge teaching were assessed with the Quality of Discharge Teaching Scale (QDTS). Data were analyzed using descriptive statistics and bivariate comparisons. Results: Of the 60 participants, 43.3% were aged 70–79 years, 58.3% were women, and 46.7% had hypertension. The mean global QDTS score was 6.2 (SD 1.6), reflecting a low perceived quality of discharge education. Conclusion: Strengthening structured educational practices and interdepartmental coordination is warranted to ensure that patients receive effective guidance for post-discharge self-care.
Keywords: Hypertension; Diabetes Mellitus; Health Education; Patient Discharge; Education; Nursing